2009
DOI: 10.1111/j.1471-6712.2008.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute – an ambiguous concept in healthcare

Abstract: The aim of this study was to explore the concept acute semantically. The concept is being used both in clinical and theoretical contexts, without questioning whether a clear meaning of the concept has been established. The analysis has been applied according to the semantic analysis strategy of the philosopher (and pedagogue) Koort (1975). First, the results show that the concept of acute has had an unclear meaning and perception in the Norwegian language. Second, the synonyms indicate two different contents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…evaluation of interventions and as Bold numbers distinguish between factor items a guide for reflection), test stability of the factors and establish cut off scores. As discussed earlier the term 'acute situations' is an ambiguous concept [10] and not related to a specific care situation or medical condition [11]. It is also important to recognize that novice nurses can be grouped into different levels of proficiency reflecting their relative experience of providing care in acute situations [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…evaluation of interventions and as Bold numbers distinguish between factor items a guide for reflection), test stability of the factors and establish cut off scores. As discussed earlier the term 'acute situations' is an ambiguous concept [10] and not related to a specific care situation or medical condition [11]. It is also important to recognize that novice nurses can be grouped into different levels of proficiency reflecting their relative experience of providing care in acute situations [7].…”
Section: Discussionmentioning
confidence: 99%
“…The semantic definition of 'acute' is sharp and intense. Synonyms also suggest something that is temporal, rapid or swift [10]. In a study describing the acute situation as a phenomenon from the perspective of novice nurses, acute situations have been considered to include significantly more than just the state of a clinically deteriorating patient.…”
Section: Introductionmentioning
confidence: 99%
“…He believes that we can begin to understand the scientific development as a historical phenomenon that is analogous to tradition, a phenomenon that can inspire practice and be modified by an emerging practice. It is here that perhaps a new ‘odd’ concept can provide something new to practice, such as Gabrielsson’s (40) analysis of the concept of ‘acute’. We may here remind us of Gadamer’s words referring to Thomas of Aquino that we have the freedom to form an infinite number of concepts and to penetrate what is meant ever more deeply (3) Each entry in the hermeneutic motion of the conceptual determination leads to something new, regardless if we start in the ontological determination of essence, or in the contextually pragmatic.…”
Section: Discussionmentioning
confidence: 99%
“…It is often described in medical terms, as something that occurs suddenly, a rapidly caused illness or injury (Lindskog, 2008). A semantic concept analysis found that acute is something that occurs suddenly but at the same time could be known to the person from a previous experience (Gabrielsen et al, 2009). This seems to be of importance being as the disease typology continues to change from acute to chronic (Potter and McKinlay, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore there is a growing population of older people (Emergency Nurses Association, 2005), who often visit the ED due to a deteriorating chronic illness (Swedish National Board of Health and Welfare, 2006), which in turn creates new demands on how the EDs are organized. The concept of emergency care does not have a clear definition in Sweden (Swedish National Board of Health and Welfare, 2011), and according to Gabrielsen et al (2009), a lack of a definition may have implications on how emergency care is organized and how the staff are able to fulfil their tasks. Little is known about the experiences of different healthcare providers working on the ''front line'' at the ED and what that entails.…”
Section: Introductionmentioning
confidence: 98%